Conventional Ankle Sprain Treatment is Associated with Alarmingly High Rates of Persistent Opioid Use. Issue 2 (25th April 2019) - Finney, Fred T.; Gossett, Timothy D.; Hu, Hsou Mei; Waljee, Jennifer; Brummett, Chad; Walton, David M; Talusan, Paul G; Holmes, James R.
Category: Ankle Introduction/Purpose: The opioid epidemic has been defined by over-prescribing by practitioners and increasing misuse, abuse, and diversion of opioids by patients. Orthopedic surgeons are the fourth largest prescriber of opioid medications and have a unique opportunity to play a prominent role in the solution. Many perceived barriers to such a solution have now been eliminated. For example, it has been demonstrated that neither the amount nor duration of opioid prescription correlates with patient satisfaction. To address this epidemic, it is important to first understand rates of new persistent opioid use following specific injuries and to identify patient-specific risk factors. In this study, we evaluated new persistent opioid use following nonoperatively treated ankle sprains, one of the most common orthopaedic injuries seen in any healthcare system. Methods: A widely accepted insurance claims database was used to identify patients who underwent nonoperative treatment of an ankle sprain between January 2008 and December 2016. None had an opioid prescription filled in the period of 12 months to 7 days prior to treatment (defined as "opioid naïve"). We evaluated peri-treatment and post-treatment opioid prescription fulfillment to analyze prescribing patterns and continuation of opioid use. The primary outcome, new persistent opioid use, was defined as opioid prescription fulfillment between 91 and 180 days after treatment. Logistic regression analysis was used to evaluate the effect of patient factors, including age, gender, median household income, tobacco use, mental health and pain disorders, and medical comorbidities on the likelihood of new persistent use. Results: 42, 445 patients were identified who underwent nonoperative treatment of an ankle sprain and received an opioid prescription. The overall rate of new persistent opioid used following nonoperative treatment of ankle sprains was 9.3%. Rates of continued opioid use were significantly increased among patients who received an opioid dose prescribed in the peri-treatment period that was in the top 25th percentile of total oral morphine equivalents. In addition, patient-specific factors which were associated with new persistent opioid use included female gender, tobacco use, certain mental health disorders, comorbid conditions, and pre-existing arthritis. Patient factors associated with lower rates of new persistent opioid use included higher level education and median household income of $100, 000 or more. Conclusion: Chronic opioid use is a major problem, even in the setting of relatively minor musculoskeletal injuries. Defining the problem and understanding contributing factors to this epidemic are paramount to developing a solution. Ankle sprains represent an orthopaedic injury which does not warrant opioid use for pain control. In this series, an alarming number of patients who sustained an ankle sprain were treated with an opioid medication, and 9.3% of these patients continued opioid use after three months. Understanding the risk factors associated with this problem provides a foundation upon which to address this sometimes lethal, public health problem.